MOVES AND GRAMMATICAL CONSTRUCTIONS OF RESEARCH ARTICLE ABSTRACTS - Leo Candra Wahyu Utami (Journal of English for Academic and Specific Purposes, 2018)
Rhetoric in writing an abstract is required for the writers’ goal which is to deliver adequate information to the readers by implementing an appropriate compositional structure of the abstract. This study aims to explore the use of grammatical construction of every rhetorical move in the research article abstracts. The result showed that grammatical constructions are found in the research article abstracts. The use of present tense is dominant in all five moves. Additionally, past tense is mostly found in method move. Active voice and passive voice are also found in all five moves. However, passive voice is frequently found in method and conclusion. In this case, the writers construct the abstract as objective as possible. That-complement clause is characteristically found in product move. Thus, implementation of this study is beneficial for the writers in academic writing to realize the use of grammatical constructions in the research article abstracts.